Estatística multivariada e análise de contrastes ortogonais aplicadas em variáveis dimensionais de bacias hidrográficas - De Barros, Bruna Soares Xavier [UNESP]; De Barros, Zacarias Xavier [UNESP]; Pollo, Ronaldo Alberto [UNESP] (My University, 2015)
In the present study, the multivariate statistics and analysis of orthogonal contrasts among means (T test) were applied to dimensional variables in third order watersheds. They were obtained by non-orbital aerial images in the Itobi city-SP, aiming at grouping watersheds of second degree of similarity, as well as detecting how representative the spatial distribution of groups is. Moreover, the orthogonal contrasts among the soils involved, regarding the Soil Map of São Paulo State from 1999, were verified by the Student´s t test. Vertical aerial photographs, 1:30000 approximate nominal scale; plani altimetric maps in 1:50000 scale (IBGE-1973) were used as cartographic basis as well as the soil maps of São Paulo state. A total of 16 watersheds distributed throughout the city were studied. The city has two predominant types of soil as follows: Alfisol and Oxisol. The dimensional variables subjected to grouping analysis discriminated 60% and 50% of watersheds considered for the Alfisol soil and Oxisol soil, respectively.
Multivariate statistics and analysis of orthogonal contrasts applied to dimensional variables of watersheds
Keywords: Multivariate analysis; Student T test; Watersheds